2009
DOI: 10.1007/s00330-008-1289-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI at 1.5 T and 3 T compared with FDG-PET-CT for the detection of tumour recurrence in patients with colorectal cancer

Abstract: The purpose of this study was to assess the diagnostic accuracy of whole-body MRI (WB-MRI) at 1.5 T or 3 T compared with FDG-PET-CT in the follow-up of patients suffering from colorectal cancer. In a retrospective study, 24 patients with a history of colorectal cancer and suspected tumour recurrence underwent FDG-PET-CT and WB-MRI with the use of parallel imaging (PAT) for follow-up. High resolution coronal T1w-TSE and STIR sequences at four body levels, HASTE imaging of the lungs, contrast-enhanced T1w- and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 42 publications
(57 reference statements)
0
61
1
9
Order By: Relevance
“…When gender proportions were reported, men were usually in the majority, with the exception of two studies 66,67 that reported mostly women and two studies 62,65 that did not report gender. The mean ages of patients when reported were 55-65 years, with a range of 33-91 years.…”
Section: Patient Populationsmentioning
confidence: 96%
See 4 more Smart Citations
“…When gender proportions were reported, men were usually in the majority, with the exception of two studies 66,67 that reported mostly women and two studies 62,65 that did not report gender. The mean ages of patients when reported were 55-65 years, with a range of 33-91 years.…”
Section: Patient Populationsmentioning
confidence: 96%
“…The distinction between cancer of the colon and rectum was not reported in four studies, 61,63,65,67 in two the population was mixed (colon and rectal disease) 66,68 and two studies reported outcomes in people with a diagnosis of rectal cancer. 62,64 …”
Section: Patient Populationsmentioning
confidence: 98%
See 3 more Smart Citations